Sikap Mahasiswa Program Studi Pendidikan Dokter Angkatan 2013 Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi terhadap Pelajaran Matematika dan Sains - Amelia Dwi Fitri; Jelpa Periantalo; Attiya Istarini (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2014)
ABSTRACT Background : Attitude that’s performed by someone can predict behaviors of the future. It shows what person will do in coming activities. Human’s attitude towards certain subject represents an important predictor that brings to academic achievement. Students who mayor in the medical faculty are the ones who naturally are interested in the subjects of mathematics and Natural science in their school. These subjects represent the main lessons that the medical students learn, even those subjects become parts of tested component selection in the entrance examination of new students. Positive attitude owned by students who have a great interest in those subjects make someone pleased in learning activities, and will cause good learning achievment. In fact, what are learnt in their interests of mathematics and science represent a condition of the lecture activities in the medical faculty. The purpose of this research is to show descriptions of Medical Students’ attitudes towards Mathematics and Science subjects. It consists of general and component descriptions about Mathematics, Physics, Chemistry and Biology. Methods : This is a descriptive research. Subjects of the researh are taken from population of the Medical Students of Jambi University the year 2013. The population of the research consists of 142 students, 45 males and 97 females. The research instrument uses attitude scale towards Mathematics and Natural Science. It has face, logic and construct validity. It has 0,92 parallel test reliability that consists of 12 items. Result : Medical students have positive attitudes towards Biology. They have neutral attitude towards Mathematics, Physics and Chemistry. There are greater positive attitude towards Biology. Very small numbers of students have negative attitude towards this subject. On Mathematics, there are more students who have positive attitude rather than negative ones. On Physics, there are twice numbers of students who have negative attitudes than positive ones. On chemistry, there are many students have positive attitudes. Conclusion: Medical students feel that learning Biology is easy and simple subject. They evaluate it positively. They think that Biology is an important and useful subject. They are always ready waiting for learning this subject in class. They feel very comfortable with this subject. Keywords: Attitude, Scale, Validity, Academic Achievement, Mathematics Science